Predictive validity of the EVARUCI scale for intensive care patients - Gomes , Larissa Milena Carvalho; Siqueira, Vitória de Barros (Revista de Enfermagem da UFPI, 2024)
Objective: To evaluate the predictive validity of the EVARUCI scale for intensive care patients. Methods: This is a retrospective longitudinal study with secondary data carried out in a reference ICU in neurology and trauma-orthopedics. The study population consisted of all users who were admitted to the ICU between January and December 2020, excluding those with a length of stay of less than 48 hours, and those who died as an outcome. Data were collected regarding admission, the first 48 hours of hospitalization and discharge. Results: The profile found was of young men, victims of external causes. The incidence of PI was 18.9%, higher EVARUCI scores were recorded on admission. The sensitivity of the test was 90.9% and 72.73%, the specificity was 16.9% and 48.9%, the positive predictive validity was 20.27% and 24.74%, and the negative validity was 88.89% and 88.46% at admission and first 48 hours, respectively. Conclusion: The scale was unable to satisfactorily predict high risk. However, it was satisfactory to predict the low risk for PI, patients who scored less than 10 on the scale were less likely to develop the lesions.